NEW APPROACHES IN TRANSLATION - Ma’ripov, Jalolxon (Scientific practical conference, 2025)
Translation is an age-old practice with roots stretching back to ancient civilizations. Historically, it has been a vital tool for cross-cultural communication, diplomacy, and the spread of knowledge. However, with the advent of technology and the increasing pace of globalization, the field of translation is undergoing a significant transformation. New approaches are redefining how translation is performed, impacting both the methodology and the role of human translators. This article explores the latest advancements in translation, focusing on neural machine translation (NMT), the integration of artificial intelligence (AI) and machine learning (ML), the role of post-editing, and the evolving function of human translators.